Epidemiology, Treatment Strategy, Natural Disease Course and Surgical Outcomes of Patients with Ulcerative Colitis in Western Hungary – A Population-based Study Between 2007 and 2018: Data from the Veszprem County Cohort. (19th September 2022) - Kurti, Zsuzsanna; Gonczi, Lorant; Lakatos, Laszlo; Golovics, Petra A; Pandur, Tunde; David, Gyula; Erdelyi, Zsuzsanna; Szita, Istvan; Lakatos, Peter L
Abstract: Background and Aims: The number of population-based studies in ulcerative colitis [UC] from Eastern Europe is limited. Our aim here was to analyse the incidence, prevalence, disease phenotype, treatment strategy, disease course and colectomy rates in a prospective population-based inception cohort including UC patients diagnosed between 2007 and 2018. The present study is a continuation of the Veszprem IBD cohort since 1977. Methods: In total, 467 UC patients were included [male/female: 236/231; median age at diagnosis: 36 years, IQR: 25–54 years]. Both in-hospital and outpatient records were collected and comprehensively reviewed. The mean length of follow-up was 8.34 ± 3.6 years. Demographic data were derived from the Hungarian Central Statistical Office. Results: The mean incidence rate was 11.02/10 5 person-years in this 12-year period. Prevalence was 317.79/10 5 persons in 2015. Disease extent at diagnosis was proctitis [E1] in 22.3%, left-sided colitis [E2] in 43.9% and extensive colitis [E3] in 33.8%. The probability of disease extent progression was 11.6% [SE: 1.8] after 5 years. The distribution of maximal therapeutic steps was 5-ASA in 46.9%, corticosteroids in 16.3%, immunosuppressives in 19.3% and biologicals in 16.5%. The probability of receiving biological therapy after diagnosis was 9.9% [SE: 1.4] at 3 years. The overall colectomy rate was 4.1% in the population. The probability of colectomy was 1.5% [SE: 0.6] at 1 year, 3.6% [SE: 0.9] at 5 years and 4.4% [SE: 1.0] at 10 years. Conclusions: The incidence of UC was high in Hungary, similar to high-incidence areas in Western Europe. Treatment strategies are in line with the biological era. The probability of progressing to proximal disease, and the medium- and long-term colectomy rates were both lower compared with data from Western European centres.